Integration of pT181-like tetracycline resistance plasmids into large staphylococcal plasmids involves IS257. - Werckenthin, C (1996)
Four large staphylococcal plasmids ranging in size from 31 to 82 kbp have been shown to mediate tetracycline resistance via an integrated copy of the tet(K)-encoding plasmid pT181 which was flanked by copies of the insertion element IS257. In two cases, IS257 elements interrupted the repC reading frame of pT181 and an 8-bp sequence from within the repC gene was duplicated at the interrupted site. In the third plasmid, the IS257 elements interrupted the pT181 DNA immediately upstream of the repC coding sequence with an 8-bp duplication. In the fourth case, the IS257 elements flanked a pT181-like plasmid with one IS257 in the repC coding sequence and the other within the recombinase (pre) coding sequence, so that a section of the pT181 sequence was deleted. All four integration sites detected in this study differ from those previously described for the IS257-mediated integration of pT181-like plasmids into large plasmids or into the chromosomal DNA.